Neonatal Meningitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The overall mortality and survival without handicap of babies with meningitis have been reviewed over a 14 year period, 1973-1986, at the Royal Maternity Hospital, and Department of Child Health, Queen's University, Belfast, Ireland.